A facile route to surface passivation of both the positive and negative defects in perovskite solar cells via a self-organized passivation layer from fullerene. (15th September 2019) - Cheng, Peng-Peng; Zhang, Yong-Wen; Liang, Jia-Ming; Tan, Wan-Yi; Chen, Xudong; Liu, Yidong; Min, Yong
Graphical abstract: Develop a facile approach to passivating both the positive and negative defects at the surface through the self-assembly of Lewis base 4, 4′-bipyridine from PCBM onto the perovskite layer via vertical phase separation. Highlights: The self-assembly of 4, 4′-bipyridine from PCBM can effectively passivate the defects. The inverted CsPbI2 Br-based PSC using PCBM:4, 4′-bipyridine yields a PCE of 12.09%. The chelation of 2, 2′-bipyridine to Pb atom promotes the formation of the δ-phase. Abstract: Planar junction perovskite solar cells without the mesoporous layer are compatible to roll-to-roll processing due to their simple and low-temperature device fabrication processing, but these perovskite films always suffer from more imperfect qualities including pin-hole formation and incomplete coverage, compared with the PSCs processed within a mesoporous scaffold. Although various approaches have been explored to obtain homogeneous, dense and highly crystalline films, there are always many defects at the film surface, acting as charge carrier trap/recombination centers. Lewis acids and Lewis base can effectively passivate negative and positive defects, respectively, but the reports on the passivation of both the positive and negative defects at one time are still quite few. Here, we introduce a facile approach to passivating both the positive and negative defects at the surface through the self-assembly of Lewis base 4, 4′-bipyridine from PCBM onto the perovskite layer via vertical phase separation. Besides, the residual bipyridine in the PCBM layer contributes to enhance its electron transport ability. As a result, the as-prepared inverted PSCs show improved device performance. To be noted, this strategy would be compatible to roll-to-roll processing, avoiding the fact that functional layers are always thickness-sensitive, which may restrict large-area high-speed roll-to-roll processing. Compared with the monodentate ligand 4, 4′-bipyridine, although the bidentate chelating ligand 2, 2′-bipyridine can passivate the trap states due to the strong interaction with the perovskite, the chelation of 2, 2′-bipyridine to Pb atom promotes the formation of the δ-phase and thus results in poor device performance.